1995
DOI: 10.1161/01.str.26.8.1463
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke as First Manifestation of Essential Thrombocythemia

Abstract: Ischemic stroke as a presenting manifestation of essential thrombocythemia is probably underrecognized. The diagnosis of thrombocythemia should not be excluded on the basis of platelet counts lower than 600 x 10(9)/L. The availability of in vitro culture of hematopoietic progenitors from peripheral blood makes it possible to diagnose early and atypical cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 14 publications
1
21
0
4
Order By: Relevance
“…Actually, both in the present study and in other series, severe thrombotic events were observed in some patients who had only moderate thrombocytosis. 10,24,25 The present study is in support of the general agreement that lowering the platelets with therapeutic agents would be indicated in high-risk ET patients with either major thrombotic or hemorrhagic complications or an age above 60 years. 5,22,26,27 However, two questions remained to be solved in prospective clinical trials.…”
Section: Discussionsupporting
confidence: 84%
“…Actually, both in the present study and in other series, severe thrombotic events were observed in some patients who had only moderate thrombocytosis. 10,24,25 The present study is in support of the general agreement that lowering the platelets with therapeutic agents would be indicated in high-risk ET patients with either major thrombotic or hemorrhagic complications or an age above 60 years. 5,22,26,27 However, two questions remained to be solved in prospective clinical trials.…”
Section: Discussionsupporting
confidence: 84%
“…4,5 At disease onset, neurologic events in our patient were attributed to ET. However, the recurrence of ischemic episodes once platelet counts returned to normal led us to consider other diagnostic possibilities, and the angiographic pattern allowed the diagnosis of moyamoya.…”
Section: Discussionmentioning
confidence: 83%
“…This has led to reportorial bias with the publication and uncritical acceptance of anecdotal and incompletely studied case reports of unexpected thrombotic events occurring in association with thrombocytosis. 242,[341][342][343] These, unfortunately, not only fail to establish a cause and effect relationship but also merely provide a numerator without any denominator. As an example, when the factors associated with hepatic vein thrombosis were evaluated retrospectively, it was found that this event was actually preceded by a high hematocrit level and followed by thrombocytosis.…”
Section: Fact Versus Fictionmentioning
confidence: 99%